Evaluation of Conservation Interventions that Use Local Knowledge and Experience at Traditional Houses Located in Kemaliye and Surrounding Settlements - Korkmaz, Ezgi; Akdemir, Mehmet Zafer (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
Located in eastern Anatolia, the Kemaliye district of Erzincan province and surrounding settlements are distinguished by unique architectural design. Due to urban migration, traditional houses in the region are not in use, leading to a gradual neglect of necessary maintenance. Climatic factors also cause varying degrees of structural damage. Flat roofs and facades of traditional houses are covered with sheet metal to prevent this damage. This method, applied with local knowledge and experience, has hidden the region's unique architecture and caused visual pollution. However, it has also ensured the preservation of these houses. Another method, the suspension of the load (emanete almak) is used to repair or replace damaged structural elements. While ensuring the general preservation of the houses, these methods have architectural impacts. The preservation of traditional settlements and architectural heritage is critical, and it is expected that local practices are in accordance with universal principles of preservation. In an effort to investigate further, the structural organization of these traditional houses, damage sustained, and sheet metal coating and suspension of the load methods of preservation are evaluated.
Keywords: Suspension of the load; traditional houses; Kemaliye; conservation interventions; local knowledge and experience; Architecture